EFFECT OF ETHICAL RECRUITMENT PROCESS AND ETHICAL ORGANIZATIONAL CULTURE ON PERFORMANCE OF STATE CORPORATIONS IN KENYA: A CASE STUDY OF KENYA REVENUE AUTHORITY - Barare, Nyamongo Ben; Wambua, Dr. Leonard (Journal of Public Policy and Administration, 2018)
Purpose: The purpose of the study was to determine the effect of ethical recruitment process and ethical organizational culture on performance of state corporations in Kenya. Methodology: The study adopted a descriptive survey. Target population was composed of 320 employees of Kenya Revenue Authority. The sample size consisted of 175 respondents who were drawn from the senior level management, middle level management and non-management staff all of whom are members of Kenya Revenue Authority. Stratified random sampling was employed in constituting the sample since it enables inclusion of all divisions in the sample. Data was obtained using questionnaires, containing both open ended and closed ended questions. The questionnaires were self-administered and they were first pilot tested for reliability and validity. Statistical package for social sciences was used for data analysis and generation of tables, figures and relationships. The data was coded and organized into concepts from which generalization was made of entire population. Data was analysed by use of descriptive statistics and inferential statistics. Quantitative data was analyzed using multi linear regression. The descriptive statistics consisted of means, percentages and frequencies. Multi linear regression was used to show the relationship between the variables. The data was presented using tables, charts and graphs. Findings: The study found that ethical recruitment process and ethical organizational culture have a positive and significant relationship with performance of state corporations. Policy Recommendations: The study recommended that organizations should ensure all their leaders are competent so as to boost their performance. In addition, scholarships and sponsorships should be made available to all staffs.